EXAMINING THE ASSOCIATION OF TEMPERAMENT AND RESILIENCE IN ELEMENTARY SCHOOL CHILDREN (The Research of Medical Science Review, 2024)
Given the unique challenges associated with human development, professionals have had an increased interest in both internal and external factors affecting the process of human development, including temperament and resilience. Therefore, current study was conceptualised to study the unique link between temperament and resilience in young children. This descriptive study explored the association of temperament with resilience in 146 children attending elementary grades and were between the age of 5 and 7 years selected through non-probability purposive sampling technique. The sample included both girls and boys, children below the age of 5 and above the age of 7 years and those with significant physical and/or developmental problems were excluded from the sample. Other than a detailed demographic form two questionnaires were used in the study to record information about children’s temperament and resilience. For temperament, the Urdu version of the Child Behavior Questionnaire (CBQ) short form was used and Child and Youth Resilience Measure was employed to measure the resilience of participants. The participants scored highest on surgency traits followed by effortful control and negative affectivity. The subdomains within the three dimensions of temperament revealed differing pattern of relationship with resilience. Understanding the association of temperament and resilience can be practically significant in enhancing well being and developing effective behaviour management pragmas.